2016
DOI: 10.1148/radiol.2015150642
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Transient Severe Motion Related to Gadoxetic Acid–enhanced MR Imaging

Abstract: Purpose To investigate the cause of imaging artifacts observed during gadoxetic acid–enhanced arterial phase imaging of the liver. Materials and Methods This HIPAA-compliant study was approved by the institutional review board. Data were collected prospectively at two sites (site A, United States; site B, Japan) from patients undergoing contrast material–enhanced MR imaging with gadoxetic acid (site A, n = 154, dose = 0.05 mmol/kg; site B, n = 130, 0.025 mmol/kg) or gadobenate dimeglumine (only site A, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
100
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 28 publications
15
100
3
Order By: Relevance
“…Interestingly, the results from different investigators show a wide range of frequencies of TSM after injection of gadoxetate disodium. The highest frequency (22 %) was observed by Motosugi et al in the USA [13]. Hayashi et al from Japan observed the lowest frequency of TSM (5 %) [11].…”
Section: Frequency Of Tsmmentioning
confidence: 88%
See 4 more Smart Citations
“…Interestingly, the results from different investigators show a wide range of frequencies of TSM after injection of gadoxetate disodium. The highest frequency (22 %) was observed by Motosugi et al in the USA [13]. Hayashi et al from Japan observed the lowest frequency of TSM (5 %) [11].…”
Section: Frequency Of Tsmmentioning
confidence: 88%
“…This assumption might explain the differences in observed frequencies of TSM. Indeed, the study sites addressing TSM used different doses of gadoxetate disodium: weight-adapted doses of 0.025 or 0.05 mmol/kg [11,13] fixed doses of 10 ml (package size) or 20 ml [6,8,10] (▶ Table 2). …”
Section: Influence Of Contrast Dosementioning
confidence: 99%
See 3 more Smart Citations